Kontribusi Ekosistem Alam dalam Meningkatkan Ketahanan Ekonomi dan Pangan Nasional di Era Perubahan Iklim yang Dinamis - Aprisanti, Rizka; El Fajri, Nur; Budijono (Badan Riset dan Inovasi Daerah Kabupaten Pelalawan, 2025)
Global climate change has had a significant impact on human life, especially in social and economic aspects. The economic resilience of communities, especially those that depend on natural resources, is becoming increasingly vulnerable due to the increase in extreme weather events, environmental degradation, and production uncertainty. In the midst of these conditions, natural ecosystems have an important role as a life buffer as well as a support for economic activity. This research aims to assess the contribution of natural ecosystems in supporting economic resilience in the era of climate change. Through this approach, researchers can synthesize various scientific findings to comprehensively explain the relationship between ecosystems and community economic resilience. This method is also useful in developing an analytical framework that will be used to discuss phenomena critically and systematically. The results of the study show that ecosystem services such as resource provision (water, food, energy), disaster management, carbon storage, and ecotourism, have high economic value and have a direct impact on community economic stability. However, ongoing damage to ecosystems threatens the sustainability of these functions. Therefore, the conservation of natural ecosystems needs to be an integral part of economic development and climate change adaptation strategies. Policy strengthening, community involvement, and the application of an ecosystem-based approach are key steps in realizing sustainable economic resilience. The policy implication of this research is the importance of integrating ecosystem service values into economic development planning, especially in the formulation of policies that support environmental protection while improving community welfare.